Behavioral Neurobiology of Anxiety and Its Treatment - Stein, Murray B.; Steckler, Thomas (Current Topics in Behavioral Neurosciences, 2010)
The book is part of a series on Current Topics in Behavioral Neurosciences, which has as its focus anxiety and its treatment. We have brought together a distinguished cadre of authors with the aim of covering a broad array of topics related to anxiety disorders, ranging from clinical diagnosis, epidemiology, preclinical neuroscience, and animal models to established and innovative therapeutic approaches. The book aims at bridging these disciplines to provide an update of literature relevant to understanding anxiety, its consequences, and its management. Following is a brief overview of the chapters and their content, meant to serve as a guide to navigating the book. The ?rst section covers clinical aspects of anxiety disorders. Joe Bienvenu and colleagues provide an incisive overview of diagnostic considerations in the anxiety disorders in which they emphasize the strengths and shortcomings of our current nosologic systems. This is followed by a review and update of the epidemiology of anxiety disorders by Ron Kessler and colleagues, which provides an authoritative survey of anxiety disorder incidence, prevalence, and risk factors. This is comp- mented by a comprehensive review of the literature on disorders that co-occur with anxiety disorders by Kathleen Merikangas and Sonja Alsemgeest Swanson. Their review highlights the tremendous comorbidity that occurs not only within the anxiety disorders, but also with other mental and physical health conditions.